"React with Cobra’s Speed to Everyday Life" On the Trap of Actuality - Andrzej Stasiuk’s Beskidy and World Chronicles (2018) - Janiec-Nyitrai, Agnieszka (Slavica, 2018)
The goal of the paper is to analyze and depict the essays written by Polish contemporary author Andrzej Stasiuk in the wider context of writing strategies. The essays were collected in Beskidy and World Chronicles (2018). The paper also deals with Stasiuk’s "workshop comments" about the art of writing and is concerned with author’s attitude to changes in social, cultural and political life. Stasiuk searches for harmony and calmness. What he writes about is not topicalities but universal themes: nature, philosophy of living, everyday life. All that he can see in mass media is very strange and outlandish for him, while he looks for eternal values, describing chaos in modern world.